2014
DOI: 10.1371/journal.ppat.1004261
|View full text |Cite
|
Sign up to set email alerts
|

Israeli Acute Paralysis Virus: Epidemiology, Pathogenesis and Implications for Honey Bee Health

Abstract: Israeli acute paralysis virus (IAPV) is a widespread RNA virus of honey bees that has been linked with colony losses. Here we describe the transmission, prevalence, and genetic traits of this virus, along with host transcriptional responses to infections. Further, we present RNAi-based strategies for limiting an important mechanism used by IAPV to subvert host defenses. Our study shows that IAPV is established as a persistent infection in honey bee populations, likely enabled by both horizontal and vertical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
262
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(277 citation statements)
references
References 33 publications
9
262
4
2
Order By: Relevance
“…Azzami et al (2012) reported that antimicrobial peptide (e.g. hymenoptaecin and abaecin) expression is not altered upon viral challenge, while a more recent study showed that IAPV infection up-regulates multiple immune signaling pathways in adult bees (Chen et al, 2014). In our study, the lack of a significant difference in viral level between treatments, in both replicate years, strongly indicates that the differences in immune system activity observed are not due to viral infection.…”
Section: Discussionsupporting
confidence: 48%
“…Azzami et al (2012) reported that antimicrobial peptide (e.g. hymenoptaecin and abaecin) expression is not altered upon viral challenge, while a more recent study showed that IAPV infection up-regulates multiple immune signaling pathways in adult bees (Chen et al, 2014). In our study, the lack of a significant difference in viral level between treatments, in both replicate years, strongly indicates that the differences in immune system activity observed are not due to viral infection.…”
Section: Discussionsupporting
confidence: 48%
“…FISH is a powerful method to determine DNA or RNA molecules in multiple types of samples. In honeybees, in situ hybridization has been applied to detect viruses such as DWV, IAPV and Kakugo virus (KV) and bacterial diseases in both adult and larval tissues (Chen et al, 2014;Fujiyuki et al, 2009;Martinson et al, 2012;Möckel, et al, 2011;Shah et al, 2009;Yue et al, 2008). In the present study, we localized IAPV in different parts of the brains of B. terrestris workers using paraffin-embedded tissue sections.…”
Section: Discussion Symptoms After Infection With Iapvmentioning
confidence: 96%
“…Despite this progress, much of our current knowledge about honey bee host-pathogen interactions is derived from sequence-based genetic, transcriptomic, and metagenomic investigations (Weinstock et al 2006;Runckel et al 2011;Chen et al 2014). As of yet, we know relatively little about honey bee immunity at the proteomic and cellular levels.…”
Section: Introductionmentioning
confidence: 99%